“Because we felt annoyed”. Emotions in the production of the political action of children that live in an occupied house - Nurit Shabel, Paula (Revista de Antropología Social, 2019)
Modern thought has been configured in dichotomies such as adulthood/infancy and thinking/feeling, which are synthesized in a permanent division between the rational and the irrational from where human action has been analyzed. However, anthropology has developed several lines of work that problematize these schemes providing alternative views on childhood and on political mobilization. In this same sense, and from an extensive ethnographic study, we propose to analyze the ways in which children between the ages of 8 and 15 living in an occupied house from the City of Buenos Aires produce collective political actions rooted in their shared emotions.
Keywords: Emotions; political action; childhood; ethnography